Perbandingan Kadar Low Density Lipoprotein dan High Density Lipoprotein Antara Akseptor KB Pil Kombinasi Dengan Depo Medroksiprogesteron Asetat - Helti Lestari Sitinjak; Rauza Sukma Rita; Yusrawati Yusrawati (Universitas Batanghari Jambi, 2019)
More than six million women worldwide use contraceptive injection and the popular contraceptive method used is contraceptive pill. Combined pill contraceptives have side effects, which are increased triglyceride and total cholesterol levels and changes in carbohydrate metabolism while the DMPA is irregular menstruation/amenorrhea, weight changes and lipid changes.This research is an observational with Cross Sectional Comparative approach to 36 combination pill acceptor and 36 DMPA acceptor. This study was conducted ini the area of Andalas and Lubuk Buaya Health Center. The sampling method used in this research was simple random sampling method. The analysis was used T-Independent test. The results showed that Low Density Lipoprotein levels DMPA (63,97 ± 12,75 mg/dl) vs combined contraceptive pill (89,66 ± 28,39 mg/dl) p = 0,25 and High Density Lipoprotein levels DMPA (63,97± 12,75 mg/dl) vs combined contraceptive pill (60,06 ± 15,57 mg/dl), p = 0,25. Results of this study concluded that there was significant difference in average of Low Density Lipoprotein and High Density Lipoprotein levels in the combined contraceptive pill and Medroxy Progesteron Acetate Depot acceptor but statistically the difference was no significant.